2006
DOI: 10.1029/2005ja011519
|View full text |Cite
|
Sign up to set email alerts
|

First results from the ionospheric radio occultations of Saturn by the Cassini spacecraft

Abstract: [1] The first set of near-equatorial occultations of the Saturn ionosphere was obtained by the Cassini spacecraft between May and September of 2005. The occultations occurred at near-equatorial latitudes, between 10°N and 10°S, at solar zenith angles from about 84°to 96°. The entry observations correspond to dusk conditions and the exit ones to dawn. An initial look at the data indicates that the average peak densities are lower and the peak altitude higher at dawn than at dusk, possibly the result of ionosphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
112
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(119 citation statements)
references
References 16 publications
6
112
1
Order By: Relevance
“…Evidence for ionisation in the Hall region is again provided by the Voyager radio occultation experiments, which show layered structures in the electron density at and below 1000 km altitude (Lindal et al, 1985). We note that similar profiles from the Cassini mission have recently been published (Nagy et al, 2006), but in their published form they do not contain sufficient detail at low altitude to be of use here. By the above formula, a layer with a vertical width of 10 km and an average electron density of 1×10 10 m −3 corresponds to ∼0.25 mho of Hall conductivity.…”
Section: Conductivities and Wind Speedsmentioning
confidence: 89%
“…Evidence for ionisation in the Hall region is again provided by the Voyager radio occultation experiments, which show layered structures in the electron density at and below 1000 km altitude (Lindal et al, 1985). We note that similar profiles from the Cassini mission have recently been published (Nagy et al, 2006), but in their published form they do not contain sufficient detail at low altitude to be of use here. By the above formula, a layer with a vertical width of 10 km and an average electron density of 1×10 10 m −3 corresponds to ∼0.25 mho of Hall conductivity.…”
Section: Conductivities and Wind Speedsmentioning
confidence: 89%
“…In addition to the solar and cosmic radiation, water inflow and particle impact have important influences on the ionospheric structure. The lower part also presents some layered structure, as it has been detected by Cassini (Nagy et al 2006). Figure 3 shows the electron concentration profile for exit (dawn terminator) measured by Pioneer 11, Voyager 1 and 2, and Cassini.…”
Section: Saturnmentioning
confidence: 99%
“…2. The number of missions to the external planets is not so comprehensive, Galileo (Hinson et al 1997) and Voyager (Hinson et al 1998) found evidence of such layers in the Jovian atmosphere, Cassini (Nagy et al 2006) in the atmosphere of Saturn and Voyager at Uranus (Strobel et al 1991) and Neptune (Lyons 1995), see Fig. 3.…”
Section: Evidence Of Meteoroid Layers Through the Solar Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Bar-Nun 1975. The importance of lightning as an agent for chemical reactions in pre-biotic circumstances was recognized even earlier, in the famous Urey-Miller experiments (Miller 1953), where electrical sparks were Ionospheric layer peak at ∼140 km / electron density ∼4 · 10 5 cm −3 Knudsen et al (1987) Mars Ionospheric layer peak at ∼120 km / electron density ∼1.5 · 10 5 cm −3 Wang and Nielsen (2003) Sporadic ionospheric layer in the range 65-110 km / electron density ∼8 · 10 3 cm −3 Pätzold et al (2005) Titan Ionospheric layer peak ∼1250 km / electron density ∼3.8 · 10 3 cm −3 Wahlund et al (2005) Atmospheric conductive layer at ∼60 km / electron density ∼650 cm −3 Jupiter Ionospheric layer peak ∼1000 km / electron density ∼10 5 cm −3 , another layer ∼2000 km with ∼10 4 cm −3 Schunk and Nagy (2000) Lower ionospheric layers (∼200 km) might attenuate HF radio waves Zarka (1985aZarka ( , 1985b Saturn Ionospheric peaks from 1200-2500 km / electron density ∼5 · 10 4 cm −3 Nagy et al (2006) Low frequency cutoff of Saturn lightning suggests diurnal variation of factor ∼100 Kaiser et al (1984) Uranus Two sharp ionospheric layers from 1500-2000 km with peak electron densities ∼10 5 cm −3 Lindal et al (1987) Neptune Ionospheric layer peak ∼1400 km / electron density ∼2.5 · 10 3 cm −3 Tyler et al (1989) used to simulate atmospheric lightning activity supposedly prevalent in the Archaean Earth. These two lines of research have since converged with many other aspects of planetary science.…”
Section: Introductionmentioning
confidence: 98%